2017
DOI: 10.1063/1.4981590
|View full text |Cite
|
Sign up to set email alerts
|

Detection of maize kernels breakage rate based on K-means clustering

Abstract: yangliangsia@sina.cnAbstract. In order to optimize the recognition accuracy of maize kernels breakage detection and improve the detection efficiency of maize kernels breakage, this paper using computer vision technology and detecting of the maize kernels breakage based on K-means clustering algorithm. First, the collected RGB images are converted into Lab images, then the original images clarity evaluation are evaluated by the energy function of Sobel 8 gradient. Finally, the detection of maize kernels breakag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Also, recent researches have demonstrated that patterns recognition technology is efficient technique to classify and identify objects and an important tool to review foods quality [20]. With the different tools generated for the image analysis it has been possible to apply it to perform analysis of grain and seed qualities [18,19,[21][22][23][24][25], and classification of seeds and fruits [5,6,[26][27][28][29], as well as the segmentation in shrimp structure [20], recognition of patterns in contamination, agricultural plants, livestock and food [4,8,[30][31][32][33]; thus it is also possible to identify diseases in different crops and rice [22,34]. By means of several techniques it is possible to determine and characterize agricultural samples to obtain different characteristics that they possess, from the experimental results that techniques generate such as signals, images, data, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent researches have demonstrated that patterns recognition technology is efficient technique to classify and identify objects and an important tool to review foods quality [20]. With the different tools generated for the image analysis it has been possible to apply it to perform analysis of grain and seed qualities [18,19,[21][22][23][24][25], and classification of seeds and fruits [5,6,[26][27][28][29], as well as the segmentation in shrimp structure [20], recognition of patterns in contamination, agricultural plants, livestock and food [4,8,[30][31][32][33]; thus it is also possible to identify diseases in different crops and rice [22,34]. By means of several techniques it is possible to determine and characterize agricultural samples to obtain different characteristics that they possess, from the experimental results that techniques generate such as signals, images, data, etc.…”
Section: Introductionmentioning
confidence: 99%